Neonatal hip septic arthritis: ultrasound should not influence decision to aspirate. Issue 3 (August 2013) - Lee, SWJ; Irwin, GJ; Huntley, JS
An 18-week-old boy presented to the emergency department with 24-h history of fever and irritability with a painful left hip held in flexion. Blood tests showed an elevated ESR of 65 mm/h, but white cell count and C-reactive protein were in the reference range. Admission hip ultrasound identified a small effusion (<2 mm at the recess), not large enough to determine turbidity. Joint aspiration under general anaesthesia yielded frank pus and mandated open arthrotomy. Physicians must maintain a high index of suspicion of hip septic arthritis irrespective of ultrasound findings and have a low threshold for joint aspiration. Aspiration 'to dryness' would have left substantial pus within the joint and is consistent with advocating arthrotomy and washout in this age group, when the diagnosis of septic arthritis has been made.